ANALYSIS OF PRODUCTION SYSTEM OF PHARMACEUTICAL COMPANY BY USING LEAN TECHNIQUE OF OVERALL EQUIPMENT EFFECTIVENESS (OEE) - Shar, Wazir Ali; Shaikh, Dr. Shakeel Ahmed; Khan, Muhammad Ali (The journal of contemporary issues in business and government, 2021)
The pharmaceutical companies generally lack maintenance equipment at working condition. However, increasing the availability of the maintenance system impacts the productivity and quality which ultimately satisfy the customers. Consequently, in order to overcome the challenges during the production system, it is necessary to implement the total quality management tool such as; total productive maintenance to enhance the productivity, quality and performance of the equipment which eventually increase the profitability of the company. So, data was collected from one of the reputed pharmaceutical company of Pakistan to evaluate the factors affecting the overall equipment effectiveness. Different analysis was carried out like fish bone diagram to find out the potential cause and Pareto chart was used to priorities the problem and also the descriptive analysis was conducted in which mean of availability, performance and quality were obtained 82.8% ,81.6% and 88.7% respectively. Total average OEE was 60%. After implementing of TPM and minimizing the six big losses. In order to minimize of losses like equipment failure, idling and minor stoppage and process defect. Our OEE was increased from 60% to 71%.